Characteristics of CH4 and CO2 emissions and influence of water and salinity in the Yellow River delta wetland, China. (August 2018) - Chen, Qingfeng; Guo, Beibei; Zhao, Changsheng; Xing, Baoxiu
Abstract: Due to the severe degradation and environmental pollution of coastal wetlands by human activities, they have gradually become an important source of greenhouse gases (GHGs) emissions, so exploring the characteristics of their emission is important to reduce greenhouse gas emissions from coastal wetlands. In this study, the dynamics of methane (CH4 ) and carbon dioxide (CO2 ) emissions were investigated in five kinds of typical tidal flats from the Yellow River delta wetland during the years 2011–2013, and the influences of water level and salinity on their emissions were explored in laboratory experiments. The mean fluxes of CO2 and CH4 were −20.98 to 68.12 mg m −2 h −1 and −0.12 to 0.44 mg m −2 h −1 across all seasons in the five kinds of representative tidal flats. The highest and lowest mean fluxes of CO2 were mainly observed during summer and winter, respectively, whereas the seasons with the highest and lowest mean fluxes of CH4 varied according to the type of tidal flat. The results showed that the summer season and the mud flat environment had the largest contributions to greenhouse gas emissions. In laboratory experiments, the largest sequestration fluxes of CO2 and CH4 were observed with +4/+2 cm and −4 cm water levels, respectively, indicating that a moderately high water level was beneficial for CO2 sequestration but led to the increase of CH4 emission. In the study of salinity, we found that the largest sequestration fluxes of CO2 and CH4 were both detected at 24 g L −1 salinity, indicating that high salinity level was advantageous for CO2 and CH4 sequestration in the five simulation devices. Furthermore, a carbon cycle pathway of coastal wetlands was proposed, which could have a vital significance for research into the global carbon cycle. We can reduce GHG emissions by protecting the coastal wetlands and lessening human activities. Graphical abstract: Image 1 Highlights: The seasonal and spatial variations of the CO2 and CH4 fluxes were different. The water level and salinity level can influence CO2 and CH4 emission fluxes. A carbon cycle pathway for coastal wetlands was proposed. Abstract : The CO2 and CH4 fluxes were different in seasonal and spatial variations and were influenced by water level and salinity; A new carbon cycle pathway of coastal wetlands was proposed.